DEVELOPING ENGLISH WRITING MATERIALS BASED ON FISHBONE TECHNIQUE FOR GRADE X STUDENTS OF SMKS AL WASHLIYAH 12 SEI RAMPAH - Prasetya, Rizky Surya; Tambusai, Azhary; Hasibuan, Ahmad Laut; Susanto, Didik (PHILOLOGY Journal of English Language and Literature, 2025)
The research aimed to develop and determine the effectiveness of the Fishbone method for improving student writing skills. This study incorporates development research as a research design. The process encompasses a research and development (R&D) cycle that includes processes such as research findings analysis, field testing, and revision. This method is used to remedy faults discovered during the field test stage. The study involved Grade Eleventh students at SMA AL WASHLIYAH 12 SEI RAMPAH, using the Ishikawa Diagram as a visual tool. The research used techniques such as study literacy, interview, observation, group discussion, and documentation. The results showed that the Fishbone method could improve student writing skills by 50%, accurately describe student needs, and be more effective than common methods. The mean percentage improvement in the experimental class was 61,39%, while in the control class it was only 30,66%.